A comparative study of the spatial distribution of schistosomiasis in Mali in 1984-1989 and 2004-2006. - Archie C A Clements; Elisa Bosqué-Oliva; Moussa Sacko; Aly Landouré; Robert Dembélé; Mamadou Traoré; Godefroy Coulibaly; Albis F Gabrielli; Alan Fenwick; Simon Brooker (Public Library of Science (PLoS), 2009)
We investigated changes in the spatial distribution of schistosomiasis in Mali following a decade of donor-funded control and a further 12 years without control.National pre-intervention cross-sectional schistosomiasis surveys were conducted in Mali in 1984-1989 (in communities) and again in 2004-2006 (in schools). Bayesian geostatistical models were built separately for each time period and on the datasets combined across time periods. In the former, data from one period were used to predict prevalence of schistosome infections for the other period, and in the latter, the models were used to determine whether spatial autocorrelation and covariate effects were consistent across periods. Schistosoma haematobium prevalence was 25.7% in 1984-1989 and 38.3% in 2004-2006; S. mansoni prevalence was 7.4% in 1984-1989 and 6.7% in 2004-2006 (note the models showed no significant difference in mean prevalence of either infection between time periods). Prevalence of both infections showed a focal spatial pattern and negative associations with distance from perennial waterbodies, which was consistent across time periods. Spatial models developed using 1984-1989 data were able to predict the distributions of both schistosome species in 2004-2006 (area under the receiver operating characteristic curve was typically >0.7) and vice versa.A decade after the apparently successful conclusion of a donor-funded schistosomiasis control programme from 1982-1992, national prevalence of schistosomiasis had rebounded to pre-intervention levels. Clusters of schistosome infections occurred in generally the same areas accross time periods, although the precise locations varied. To achieve long-term control, it is essential to plan for sustainability of ongoing interventions, including stengthening endemic country health systems.